Rancang Bangun Sistem Monitoring dan Kendali Suhu Ruangan Berbasis Internet of Things - Helfy Susilawati; Adira Nur Andiyani; Sifa Nurpadillah (CYCLOTRON, 2023)
Room temperature monitoring and control system in the pharmaceutical industry is an important aspect in the process of production and storage of pharmaceutical products. Implementing a technology-based system, it can facilitate users in monitoring and controlling room temperature. This study designed a system of monitoring and control of room temperature in herbal medicine company. This system is designed by using microcontroller NodeMCU ESP8266, DHT11 as a temperature detector, SG90 servo as a button pusher on the remote central AC, and website utilization as interface for monitoring and controlling room. When the room temperature doesn’t match the reference, then the user can give the command to the mechanical controller to change the temperature on the remote using the controls on the website. Based on the test results, the readings of the three DHT11 sensors are still within tolerance limits, with each average temperature reading error of 0.71%, 0.51%, and 1.32%